Rede de Atenção Psicossocial na interface com a população em situação de rua: entre o instituído e o instituinte - Paiva, Irismar Karla Sarmento de (2019)
This research brings up the interface Psychosocial Care Network (PCN) and Homeless Persons (HPs). These people have historically been relegated to the commonplace of crime and madness, constituting a challenge for health services, which requires us to break with the institutionalizing and bureaucratized ways of producing health towards a true integration among actors/services/social movements in line with the principles of the Brazilian Sanitary Reform (BSR) and of the Brazilian Psychiatric Reform (BPR). The core objective of this paper is to analyze how the articulation among the services of the Psychosocial Care Network in Natal/RN is performed in the perspective of the comprehensive care for the homeless persons. This is a qualitative research with descriptive-exploratory approach, guided by the light of dialectical historical thought. Data collection took place by means of the circulation of ten services representing the five Health Districts that integrate the components of the Psychosocial Care Network in Natal/RN, establishment of a focus group with professionals of this Network and semi-structured interviews with 13 homeless citizens who were users of these services. It received the approval from the Research Ethics Committee of the Onofre Lopes University Hospital of the Federal University of Rio Grande do Norte (HUOL-UFRN) on August 9th, 2018 – CAAE 92971818.1.0000.5292 and opinion nº 2.809.420. The construction of the results entailed movements from concrete to abstract, from singular to plural, seeking new references that illuminate the research object. The results were systematized on the basis of the Minayo’s operational proposal, drawing up the following analytical categories: Homeless Persons in the Psychosocial Care Network: from white blindness to black numbers, where we discuss how PCN sees the Homeless Persons. These people, when not invisible, are associated with stigmas and labels that refer them to places of discredit, street of exception, i.e., deathly life. Regarding the access of the Homeless Persons to the mental health services, we can identify numerous barriers that separate the places of care from the empty place of the (de) territorialized individuals. Faced with this model of lack of care, we should place our bet on the processes of singularization as a challenge to introduce care to these people. Psychosocial Care Network: on the tightrope of the care structure, which consists of a Network balance performed through the challenges for deinstitutionalization of madness. Although we have been identified in this category obstacles that walk against the Brazilian Psychiatric Reform, we recognize potentialities that favor its effectiveness in the instituting forces that are arranged in a micropolitics of the desire. In summary, the interface Psychosocial Care Network and Homeless Persons has vulnerabilities, being this public relegated to a kind of exile landscape that hampers the achievement of the right to health. Moreover, the living condition of the public in question requires us to consider the different ways of inhabiting and circulating in the city, the inclusion of diversity and the production of new sociabilities. We hope that the results may serve as a way of contributing to the feasibility of a national policy for homeless persons in the locoregional context; and, in the molar dimension, we intend to activate instituting ways of fostering the Brazilian Psychiatric Reform and the defense of the right to health as a matter of citizenship.